Converting to Otherness, Islam, Autobiography and Embracing the Other (KEMANUSIAAN The Asian Journal of Humanities, 2019)
For Muhammad Asad, converting to Islam was a matter of continuity not disjunction with his identity as a Jew. The disavowal happened with his identity as a European in a materialistic context. His symbolic battle is launched against his Western heritage with all its attendant anti-Semitism and fascism that claimed the lives of his father and sister. This symbolic battle is clear in his autobiography, The Road to Mecca (1954). Islam provided Asad with a space from which he could critique Western modernity which is centred around the material. On the other hand, in her autobiography, From MTV to Mecca: How Islam Inspired My Life (2012), Kristiane Backer created a “third space” where she tried to reconcile two selves in one subjectivity. The otherness of Islam is tempered by the internal conversion experience of the new Muslim. So instead of looking at conversion as a radical act that negatively affected her original culture, Backer tried to form some continuity with her past self.